THE RELATIONSHIP BETWEEN MOTHER'S PHYSICAL ACTIVITY WITH THE LONG TIME OF LABOR PROCESSES IN REGION OF PUSKESMAS SINDANG BARANG KOTA BOGOR IN 2018: HUBUNGAN ANTARA AKTIVITAS FISIK IBU DENGAN LAMANYA PROSES PERSALINAN DI WILAYAHPUSKESMAS SINDANG BARANG KOTA BOGOR TAHUN 2018 - Magdalena Magdalena Agu Yosali; dr. Astry dr. Astry (Wijaya Husada, 2019)
The Maternal Mortality Rate (MMR) is one indicator that can describe the welfare of the community in a country. According to the World Health Organization (WHO) in 2012 as many 99% of maternal death’s were caused by labor problems. The Maternal Mortality Rate (MMR) in developing countries is the highest compared to MMR in the depeloved countrieswith a total 450 deaths/ 100.000 live births. This is very important, considering the high MMR associated with pregnancy, childbirt, nipas, beside being coused due to complication also coused by several complicating factor of labor that effect the length of labor, including age, parity, distance of pregnancy, activity during pregnancy, antenatal care visit. This type of research is quantitative analytical methods. The study was conducted at the Sindang Barang health center Bogor City in 2018, totaling with 45 respondents. Using the total sampling technique. The instrument used were physical activity questionnaires and partograph sheets while data analysis techniques used univariate and bivariate analysis. In the statistical test of study of the relationship between maternal physical activity and the length of labor in Sindang Barang Health Center Bogor city 2018, it can be concluded that there are 20 (44,44%) mothers with long-term labor activity > 24 hours, there are 1 (22,2%) mothers with heavy activity that experience normal labor < 24 hours, there 9 (24,4%) mothers with strenuous activity who experience prolong labor > 18 hours, there are 2 (4,45%) mothers with heavy activity who experience < 18 hours. There are 1 (2,22%) mothers with mild activity who experience prolonged labor > 24 hours, there are 3 (6,67%) mothers with mild activity who experience normal labor < 24 hours, there are 2 (4,45%) mothers with mild activity who experience prolonged labor > 18 hours, there are 7 (15,55%) mothers with mild activity who experience normal delivery < 18 hours. Based on the results of the value of P value 0.000 is obtained so that the alternative hypothesis is accept and the null hypothesis is riject. So that there is Relationship between Mother’s physical Activity and the Length of Labor in the Sindang Barang Health Center in Area Bogor City 2018.